Aktivitas Antibakteri Ekstrak dan Fraksi Daun Manggis (Garcinia mangostana) terhadap Staphylococcus aureus dan Pseudomonas aeruginosa - Ghani Nurfiana Fatma Sari; Taufik Turahman (Prosiding Seminar Nasional Unimus, 2018)
Infectious diseases are still one of the important public health problems to be considered, especially in developing countries. Mangosteen Leaves (Garcinia mangostana L.) is one of the well-known plants that are useful as antioxidants, antibacterial, and anticancer. This study aims to determine the chemical content and antibacterial activity of ethanol extract, n-hexane fraction, ethyl acetate and water of mangosteen leaves (Garcinia mangostana L.) on diffuse Staphylococcus aureus and Pseudomonas aeruginosa. Mangosteen leaves were extracted by maceration using 96% ethanol then continued by fractionation using a liquid-liquid extraction method. Mangosteen leaf extract and the fraction obtained were then tested for antibacterial activity with a concentration of 12.5%, 25% and 50% using disc diffusion method. The positive control used was ciprofloxacin 5μg / disk and negative control using 5% Tween 80. Identification of compound groups can be done using Thin Layer Chromatography (TLC) method. The results of antibacterial activity testing showed the zone diameter inhibition of gram-positive bacteria generally tends to be greater than gram-negative bacteria. The diameter of the largest inhibitory zone in Staphylococcus aureus bacteria is found in the water fraction of mangosteen leaves at 50% concentration with inhibitory zone diameter (10 mm), in Pseudomonas aeruginosa bacteria found in the water fraction and extract with a concentration of 50% has a inhibitory power of (8 mm). The TLC test results showed that in the extracts and fractions of mangosteen leaves contained flavonoids, saponins and steroids.